Effect of protein polymorphisms on milk composition, coagulation properties, and protein profile in dairy sheep - Marshall AC; Vigolo V; De Marchi M; Lopez-Villalobos N; Loveday SM; Weeks M; McNabb W (Elsevier Ltd, 2025)
The objective of this study was to quantify the effect of protein polymorphisms on milk composition, coagulation properties, and protein profile in dairy sheep from a New Zealand flock. A total of 470 test-day records, from 147 lactating ewes, were used in the statistical analyses. Protein polymorphisms observed in the RP-HPLC were self-named for purposes of the present study. Data were analyzed using a mixed linear model, including the fixed effects of ewe age, litter size, coat-colour, and stage of lactation, and, as a covariate, deviation from the median lambing date of the flock. The effects of protein polymorphisms were added to the model, one at a time. Protein polymorphisms were significantly (p < 0.05) associated with milk composition and protein profile. Polymorphisms of β-lactoglobulin were significantly associated with milk heat stability, being AB type more heat stable than AA. The other processability traits were not significantly affected by protein polymorphisms. Further studies are required to confirm the protein variants and the properties of individual protein polymorphisms.
Keywords: Sheep milk; Dairy sheep; Milk composition; Protein profile; Milk coagulation; Heat stability